Desenvolvimento de uma metodologia de desinfestação da alga gracilaria caudata por plasma dbd - Morais, Camila Jesiele Oliveira (2017)
The existence of pathogenic microorganisms in food products has been one of the major causes of food-related diseases and is one of the limiting factors for the development of in vitro culture techniques that require complete decontamination. Despite the increasing importance of algae in different fields, which has led to a drop in their natural stocks, studies related to this problem are still limited when compared to plants. Existing disinfestation methodologies for algae follow numerous steps, as they present markedly fragile structures, and often use antibiotics in the process. Based on that, this work aimed the development of an efficient disinfestation methodology for this type of organisms, specifically the algae Gracilaria caudata. Two disinfestation processes were performed: a chemical and a physicochemical process. The first one consisted in the use of a NaClO solution to obtain a few steps simplified protocol. The explants were submitted to treatments with concentrations of 0.01, 0.05, 0.5 and 1%, as well as a commercial solution of 0.5% NaClO, and each concentration was applied during different contact times: 5 and 30 seconds, 1, 5 and 10 minutes. The second method consisted of using a dielectric barrier discharge (DBD) plasma system for decontamination of the surfaces (10 and 20 minutes of exposure), which allows, in addition to the simplicity of the procedure, the non-use of toxic reagents. The gas used in this procedure was helium. The results exhibited 100% decontamination for the concentration of 1% NaClO (10 minutes), commercial solution (5 and 10 minutes) and for the treatment with DBD plasma for the two treatment times performed: 10 and 20 minutes. Although the achievement of a complete decontamination for the chemical methodology, a clear discoloration of the algae was observed shortly after the treatment, whereas for the physicochemical treatment the same aggressiveness was not observed, emphasizing that coloration is a determinant factor of the health of these tissues. In this way, the treatment with DBD plasma emerges as an ecologically clean alternative in the decontamination of biological surfaces, making possible the use of treated algae for different applications